2009
DOI: 10.1002/adma.200803439
|View full text |Cite
|
Sign up to set email alerts
|

Designed Synthesis of Coaxial SnO2@carbon Hollow Nanospheres for Highly Reversible Lithium Storage

Abstract: A proof‐of‐concept structural design is demonstrated for high‐capacity lithium‐ion batteries anode materials by multistep synthesis of coaxial SnO2@carbon hollow nanospheres. This material integrates two beneficial features: hollow structure and carbon nanopainting. When evaluated for reversible lithium storage, these functional materials manifest excellent cycling performance and rate capabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
783
2
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,024 publications
(817 citation statements)
references
References 31 publications
(32 reference statements)
22
783
2
3
Order By: Relevance
“…3c and d, it can be observed that the graphene sheets are distributed between the SnO 2 nanoparticles and the nanoporous composite with large amount of void spaces was formed [30]. Such porous nanocomposite can possess excellent cycle performance as an anode material for lithium-ion batteries due to the large amount of void spaces which could buffer large volume changes of SnO 2 nanoparticles during lithium ions insertion/extraction process [7,8,12,16,18,30,38]. Moreover, the graphene sheets distributed between the SnO 2 nanoparticles can prevent the aggregation of these nanoparticles to a certain extent [9,14,25,32,38], which can be of great benefit to cycle life.…”
Section: Microstructural Characterizationmentioning
confidence: 98%
See 3 more Smart Citations
“…3c and d, it can be observed that the graphene sheets are distributed between the SnO 2 nanoparticles and the nanoporous composite with large amount of void spaces was formed [30]. Such porous nanocomposite can possess excellent cycle performance as an anode material for lithium-ion batteries due to the large amount of void spaces which could buffer large volume changes of SnO 2 nanoparticles during lithium ions insertion/extraction process [7,8,12,16,18,30,38]. Moreover, the graphene sheets distributed between the SnO 2 nanoparticles can prevent the aggregation of these nanoparticles to a certain extent [9,14,25,32,38], which can be of great benefit to cycle life.…”
Section: Microstructural Characterizationmentioning
confidence: 98%
“…The increased pore volume could arises primarily from the formation of secondary pores between the SnO 2 nanoparticles and graphene sheets as well as the close stacking of graphene sheets distributed between the SnO 2 nanoparticles [38]. The nanopores in SnO 2 /graphene nanocomposite could act as buffering spaces against the volume changes of SnO 2 nanoparticles during lithium ion insertion/extraction process [7,8,13,14,18,38], which would lead to enhanced cycling stability as an anode material for lithiumion batteries.…”
Section: Microstructural Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor cycle life) due to the volume change and pulverization of electrode during alloying-dealloying (Cherian et al 2013b;Lou et al 2009). To overcome these problems, two different approaches have been adapted by researchers to improve cyclability and maintain high capacity, first, to use nanostructured tin compounds (Cherian et al 2013b) and second to use carbon-SnO 2 matrix which acts as buffer to reduce the strain during lithiationdelithiation.…”
Section: Introductionmentioning
confidence: 99%